Insights into the Dissolution Kinetics of NaLAS Tablets. Issue 6 (7th September 2017) - Pan, Bochen; Shen, Rui; Guan, Zhe; Li, Jiapeng; Jiang, Jun; Tong, Yao; Dang, Leping; Wei, Hongyuan
Abstract: In this work, the dissolution behaviors of a series of sodium alkylbenzenesulfonates (NaLAS) tablets with different moisture contents and neutralization degrees were investigated in aqueous solution. The ANOVA‐based, model‐independent and model‐dependent methods were employed to perform comparison analyses on dissolution profiles. The measurements of powder X‐ray diffraction patterns and mechanical properties elucidate distinct differences in each formula. The results show that ANOVA provides a possibility for finding the source of differences among different variables, and the model‐independent methods including the k values and mean dissolution time are easy to interpret and perform comparison analyses. The Hixson–Crowell model gives satisfactory correlation results for the dissolution data and the dissolution kinetics parameters are obtained. The inhibition effects of neutralization degree and moisture content on NaLAS dissolution were examined, which reveals that the increase in lamellar phase proportion leads to the reduction of dissolution rate. The comparison analyses performed in this work form part of a methodology for dissolution profile prediction and comparison.